Structurally complex farms support high avian functional diversity in tropical montane Ethiopia - Gove, Aaron; Hylander, K.; Nemomisa, S.; Shimelis, A.; Enkossa, W. (Cambridge University Press, 2013)
Of all feeding guilds, understorey insectivores are thought to be most sensitive to disturbance and forest conversion. We compared the composition of bird feeding guilds in tropical forest fragments with adjacent agro-ecosystems in a montane region of south-west Ethiopia. We used a series of point counts to survey birds in 19 agriculture and 19 forest sites and recorded tree species within each farm across an area of 40 × 35 km. Insectivores (~17 spp. per plot), frugivores (~3 spp. per plot) and omnivores (~5 spp. per plot) maintained species density across habitats, while granivores and nectarivores increased in the agricultural sites by factors of 7 and 3 respectively. Species accumulation curves of each guild were equal or steeper in agriculture, suggesting that agricultural and forest landscapes were equally heterogeneous for all bird guilds. Counter to most published studies, we found no decline in insectivore species richness with forest conversion. However, species composition differed between the two habitats, with certain forest specialists replaced by other species within each feeding guild. We suggest that the lack of difference in insectivorous species numbers between forest and agriculture in this region is due to the benign nature of the agricultural habitat, but also due to a regional species pool which contains many bird species which are adapted to open habitats.